Legal Dualism in Native Christian Marriage Law in The Dutch East Indies (19th–20th Centuries) - Juwono, Harto (Sekolah Tinggi Teologi Injili Indonesia Surabaya, 2025)
This study analyzes the legal status of marriage among native Christians within the dualistic legal system of the Dutch East Indies during the 19th and 20th centuries. The main issue is the contestation between church law and colonial civil law, which affected the legality of native Christian marriages. The research employs a structural historical approach, utilizing colonial archival sources and church documents. The findings reveal that the Dutch colonial government implemented ambivalent policies that created structural tension between ecclesiastical and state authority. This legal dualism resulted in legal uncertainty for native Christian marriages recognized by the church but not always acknowledged by colonial civil law. The study contributes to a deeper understanding of colonial legal dynamics and their impact on indigenous communities.